2022
DOI: 10.1371/journal.pone.0264167
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of statistical methodology used to evaluate progression of chronic kidney disease using electronic healthcare records

Abstract: Background Electronic healthcare records (EHRs) are a useful resource to study chronic kidney disease (CKD) progression prior to starting dialysis, but pose methodological challenges as kidney function tests are not done on everybody, nor are tests evenly spaced. We sought to review previous research of CKD progression using renal function tests in EHRs, investigating methodology used and investigators’ recognition of data quality issues. Methods and findings We searched for studies investigating CKD progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Second, loss to follow-up could cause selection bias, especially if unhealthy people are more likely to be lost to follow-up. 7 In the present study, older people and women were more likely to quit the JMDC database. We speculate that the main reasons for the loss to follow-up were social (e.g., retirement at age 60-65, retirement due to pregnancy and childbirth) and not directly associated with the health status of study participants, but we could not confirm the exact reasons.…”
Section: Resultsmentioning
confidence: 48%
See 3 more Smart Citations
“…Second, loss to follow-up could cause selection bias, especially if unhealthy people are more likely to be lost to follow-up. 7 In the present study, older people and women were more likely to quit the JMDC database. We speculate that the main reasons for the loss to follow-up were social (e.g., retirement at age 60-65, retirement due to pregnancy and childbirth) and not directly associated with the health status of study participants, but we could not confirm the exact reasons.…”
Section: Resultsmentioning
confidence: 48%
“…The strength of this study is that we used consecutive 10-year annual health checkup data for the general adult population. A systematic review of kidney disease progression 7 indicated that following the same population for a long time is practically difficult, and only one study was reported to achieve the mean follow-up of over 10 years. 35 The mandatory health checkup system for people aged 40–74 years in Japan made the present study feasible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations